Simulación de circuitos eléctricos RLC en resonancia. - Bravo Ludeña, Jhon Oliver (2008)
The progress of computing and computing today allows us to have software that facilitates simulations of Electrical and Electronic Circuits, one of them is the ELECTRONICS WORKBENCH program which is one of the most used in different higher education centers. In our case it has been limited its use by the students to carry out the practices of these circuits, due to lack of computational resources. In this program there are virtual devices such as: resistors, inductances, capacitances, diodes, earthing, AC and DC voltage sources; Measurement instruments such as: ammeters, voltmeters, ohmmeters, oscilloscopes, frequency meters, in which different types of electrical measurements can be made, the same way we have the possibility to execute serial, parallel and mixed connections of the RLC electrical circuits. In the devices that are in this program can be determined any value to each of them, thus allowing us to operate the values of the devices, to achieve different representations. It is also possible to verify if the measurements obtained compensate the calculations made with the different scientific procedures that pertain to each electric circuit.